Balance Sheet Analysis in Fund Surveillance : Reference Note. (Policy Papers; Policy Paper ;, 2015)
This note serves as a reference for balance sheet analysis, which should be read in conjunction with the IMF board paper on Balance Sheet Analysis in Fund Surveillance. It provides a: compendium of good examples of balance sheet analysis from both bilateral and multilateral surveillance, covering a variety of topics; full listing of available balance sheet related macro datasets, including their relevance for surveillance, remaining limitations, and remedial measures being undertaken; summary of data availability for each Fund member; compilation of all the tools for balance sheet analysis developed by the Fund over the last decade; and toolkit featuring some new empirical applications that could help deepen balance sheet analysis in surveillance. These include illustrations of how to construct and use BSA matrices, general equilibrium and reduced form approaches, as well as tools to analyze sectoral vulnerabilities using micro data.